Flavour compounds affect protein structure: The effect of methyl anthranilate on bovine serum albumin conformation. (15th September 2022) - Dinu, Vlad; Borah, Pallab Kumar; Muleya, Molly; Scott, David J; Lithgo, Ryan; Pattem, Jacob; Harding, Stephen E.; Yakubov, Gleb E.; Fisk, Ian D.
Highlights: The binding of methyl anthranilate with bovine serum albumin (BSA) was investigated. Methyl anthranilate binds to BSA, resulting in protein compaction. Molecular modelling suggests methyl anthranilate binds to the Sudlow II site of BSA. Abstract: This study aims to understand possible effects of flavour compounds on the structure and conformation of endogenous proteins. Using methyl anthranilate (a grape flavour compound added to drinks, confectionery, and vape-liquids) and bovine serum albumin (BSA, a model serum protein) we designed experimental investigations using analytical ultracentrifugation, size exclusion chromatography small angle X-ray scattering, and fluorescence spectroscopy to reveal that methyl anthranilate spontaneously binds to BSA ( ΔG°, ca. −21 KJ mol −1 ) which induces a conformational compactness (ca. 10 %) in the monomer structure. Complementary molecular modelling and dynamics simulations suggested the binding occurs at Sudlow II of BSA via establishment of hydrogen bonds with arginine 409, lysine 413 and serine 488 leading to an increased conformational order in domains IA, IIB and IIIB. This work aims to set the foundation for future research on flavour-protein interactions and offer new sets of opportunities for understanding the effects of small compounds on protein structure.